Itaconate family-based host-directed therapeutics for infections - Yuk, Jae-Min; Park, Eun-Jin; Kim, In Soo; Jo, Eun-Kyeong (Frontiers in Immunology, 2023)
Itaconate is a crucial anti-infective and anti-inflammatory immunometabolite that accumulates upon disruption of the Krebs cycle in effector macrophages undergoing inflammatory stress. Esterified derivatives of itaconate (4-octyl itaconate and dimethyl itaconate) and its isomers (mesaconate and citraconate) are promising candidate drugs for inflammation and infection. Several itaconate family members participate in host defense, immune and metabolic modulation, and amelioration of infection, although opposite effects have also been reported. However, the precise mechanisms by which itaconate and its family members exert its effects are not fully understood. In addition, contradictory results in different experimental settings and a lack of clinical data make it difficult to draw definitive conclusions about the therapeutic potential of itaconate. Here we review how the immune response gene 1-itaconate pathway is activated during infection and its role in host defense and pathogenesis in a context-dependent manner. Certain pathogens can use itaconate to establish infections. Finally, we briefly discuss the major mechanisms by which itaconate family members exert antimicrobial effects. To thoroughly comprehend how itaconate exerts its anti-inflammatory and antimicrobial effects, additional research on the actual mechanism of action is necessary. This review examines the current state of itaconate research in infection and identifies the key challenges and opportunities for future research in this field.